Antiproliferative activity of morpholine-based compounds on MCF-7 breast cancer, colon carcinoma C26, and normal fibroblast NIH-3T3 cell lines and study of their binding affinity to calf thymus-DNA and bovine serum albumin. Issue 14 (22nd September 2019) - Hosseini-Kharat, Mahboubeh; Rahimi, Rahmatollah; Zargarian, Davit; Mehri Lighvan, Zohreh; Momtazi-Borojeni, Amir Abbas; Sharifi, Tayebeh; Abdollahi, Elham; Tavakol, Hossein; Mohammadi, Tecush
Abstract: This report describes the results of a study on the antiproliferative activity of the morpholine-based ligand 1, 3-bis(1-morpholinothiocarbonyl)benzene (HL ) and its nickel(II) complex (NiL ) against human breast cancer cells (MCF-7), colon carcinoma cells (C26), and normal fibroblast NIH-3T3 cells. NiL showed better cytotoxicity on both cancerous cells relative to normal cells in vitro with the highest selective index of 2.22 in MCF-7 cells. The interaction of both compounds with calf thymus DNA (CT DNA) and bovine serum albumin (BSA) was studied using various spectroscopic techniques and analytical methods such as UV − vis titrations, thermal denaturation, circular dichroism, competitive fluorescent intercalator displacement assays, as well as molecular modeling. The fluorescence intensity of the probe molecule increases clearly when HL and NiL are added to the methylene blue (MB)–DNA system. Furthermore, the binding of HL and NiL quenches the BSA fluorescence, revealing a 1:1 interaction with a binding constant of about 10 5  M −1 . Communicated by Ramaswamy H. Sarma